Hemodynamics and the Development of Certain Malformations of the Great Arteries Comment Vorgelegt in der Sitzung vom 18. November 1989 von Wilhelm Doerr - Conte, Giuseppe; Giannessi, Francesco; Cornali, Mario; Chuaqui, Benedicto (Sitzungsber.Heidelberg 90, 1990)
Experimental results reached by the authors as well as various hypotheses previously advanced by other research workers are examined in this volume. The authors' study of the course of bloodstreams in the ventricular outflow tract and in the 6th and 4th branchial arterial arches points to 13 hemodynamic patterns and 13 changes in the direction of the endocardial septal ridges. They describe the hemodynamic processes of development of several well-known malformations of the great arteries and of other vascular anomalies that have not been identified morphologically. The authors conclude that it is possible in this way to correctly explain the cardiovascular malformations that have been obtained experimentally